Pengetahuan Ibu tentang Deteksi Stunting - Hunggumila, Antonetha; Aziza, Waviq; Radandima, Ester (JURNAL KESEHATAN PRIMER, 2022)
Background:  Stunting is a growth disorder resulting from a lack of nutritional intake over a long period of time.  Children who experience stunting will grow up to be shorter than their peers, often without their families realizing it.   Stunting has an impact on intelligence levels, susceptibility to disease, decreased productivity.  The aim of this research is to find out.  Mother's knowledge about early detection of toddler growth and development as an effort to prevent stunting in Kawangu Village, Kawangu Community Health Center working area, East Sumba Regency.  Method: This type of research is a descriptive method with a quantitative research type. The sample used was 30 mothers of toddlers in Kawangu Village in 2022. The sampling technique used was a purposive sampling technique, namely a questionnaire.  The data was analyzed univariately. Results: research found that the knowledge of mothers of toddlers about early detection and prevention of stunting was in the sufficient category at 63%, at 30% poor and at 7% good.